TANGGUNG JAWAB NOTARIS DALAM HAL MELAKUKAN PELANGGARAN PASAL 17 UNDANG-UNDANG NOMOR NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS - Hj. Rianda Riviyusnita (Fakultas Hukum Universitas IBA Palembang, 2021)
The position or profession of a Notary is a position of trust that is responsible both legally, morally and ethically to the State or government, society, parties concerned (clients) and professional organizations, so that the quality of a Notary must always be improved through education, understanding and deepening of science and code of ethics. A Notary Public has the authority, obligations and prohibitions that they must obey in carrying out their duties. If a violation occurs, a Notary can be held accountable. In UUJN the accountability for Notaries who hold concurrent positions is also regulated in Article 38 letter e of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 25 of 2014 concerning Terms and Procedures for the Appointment, Transfer, Dismissal and Extension of the Notary's Term of Office, which further explains the provisions concerning Notary who can be dismissed with respect from his position, if concurrently as a civil servant, state official, lawyer, or is currently holding another position which is prohibited by law to be concurrently with the position of Notary.